Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
y = [tex]-\frac{2}{3}x + 1[/tex]
Step-by-step explanation:
When y = mx + b
I. Find m.value
If m = (y2 - y1) / (x2 - x1)
= ( -1 - 3) / (3 + 3)
= -4/6
m = -2/3
II. Find b.value
If y = mx + b, when y is 3, x is -3 and m is -2/3
3 = -2/3(-3) + b
3 = -2(-1) + b
3 = 2 + b
3-2 = b
b = 1
That makes y = -2/3(x) + 1
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.